Manajemen Pengelolaan Wisata Sumber Jiput - Ayu, Natasya Dia; Anggraeni, Nofa Ageng; Annisa, Nove (Fakultas Tarbiyah IAIN Kediri, 2023)
Tourism is an integral part of human life, especially regarding socio-economic activities. Sumber Jiput Tourism is a tour that still exists and is still visited by many people. The role of the local community in the management of the Jiput source tourism object is very important for the continuation of tourism and tourists. The Karang Taruna community is the manager as well as the tourism cultivator. With the times and also the existence of assistance from the Kediri government's youth tourism culture and sports department, the management of the Jiput source tourism continues to improve ideas to further develop it to become even more interesting and better. Because the source of Jiput is well-known as a water source destination whose existence is still very prominent among the people of Kediri. Management that is still lacking and has not been implemented properly must be repaired immediately. The research method used is descriptive qualitative. Determination of informants using purposive sampling, namely representative. There are two types of data sources, namely primary data sources and secondary data. Data collection techniques are in-depth interviews, observation, documentation. The way to analyze the data is data sorting, data presentation and integrated enumeration. The results of the study show that the management of marketing, human resources and finance is currently running well, so that it influences the existence of this Jiput tourism source.